Path-Loss Optimized Indoor Laser-Based Visible Light Communication System for Variable Link Length Gigabit-Class Communication - Faheem Ahmad; Sathisha Ramachandrapura; Jyothsna Manattayil; Varun Raghunathan (IEEE Photonics Journal)
We discuss an optical ray-tracing approach to minimizing path-loss in a variable link length indoor blue laser down-converted white light visible light communication (VLC) system. For a given link length, minimum path-loss is achieved by finding optimum positions of transmitter and receiver lenses relative to phosphor and detector respectively such that collection efficiency is maximized. The designed VLC system is experimentally implemented for two different optimized link lengths of 25 and 300 cm. The down-converted white light for the optimized link is found to exhibits narrow beam spread, spot-lighting type illumination profile. The white light is measured to quantify the beam profile, color rendering, illuminance and percentage of blue-content. The illumination beam profile and propagation characteristics are found to be in good agreement with optical simulations. Communication experiments with on-off modulated at 1.5 Gbps achieved BER of ∼3 × 10−3 for the optimized link, which is below the forward-error correction threshold. The above communication performance is achieved at illumination levels at the receiver as low as ∼45 and 16 lx. Comparison with previous laser-based VLC implementations shows that the path-loss optimization helps achieve gigabit-class communication at practically relevant link lengths and the lowest illuminance levels thus far reported. Such low illuminance level, narrow beam spread VLC luminaires can potentially coexist with existing lighting infrastructure for eye-safe indoor applications.